THE FAILURE OF AN EFFECTIVE HUMANITARIAN RESPONSE TO PROTECT SUB-SAHARAN AFRICAN REFUGEES AND ASYLUM SEEKERS - Garbout, Wafa (2021)
Throughout its history, Tunisia has never been an immigration country until recently following the outbreak of the Libyan civil war in 2011. During their migratory journey to reach Tunisia as a transit or a destination country, Sub-Saharan Africans on the move face various human rights violations that may also be considered as crimes against humanity, including killing, kidnapping, torture, and extortion, as well as rape and other degrading practices conducted by the human traffickers and smugglers or inside detention centers controlled by armed militias. When reaching Tunisia through land or when being intercepted in the Mediterranean by the Tunisian coastal guards while they are trying to get to Europe, Sub-Saharan Africans on the move seek asylum and protection through UNHCR as the entity that has the authority of refugee status determination RSD, considering the absence of national asylum law in Tunisia. This paper seeks to highlight the failure of an effective humanitarian response by the Tunisian government and the international community to protect Sub-Saharan Africans on the move. Likewise, this paper seeks to accentuate the urgent need to protect the vulnerable Sub-Saharan Africans on the move in Tunisia in light of the rise of xenophobia, racism, and hate crimes towards them. This paper also tries to study and analyze the core reasons and factors that led to this humanitarian crisis and the failure to solve it.